AL-TARAKIIB AL-‘ARABIYYAH AL-MUSTA’MALAH FII AL-LUGHAH AL-INDUUNISIYYAH: ‘ADDADUHA WA ANWAA’UHA WA KHASHAAISHUHAA - Lubis, Torkis (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2011)
This article describes Arabic phrase and sentence adopted from Bahasa Indonesia to answer three main questions on language absorption, mainly: how many Arabic phrase and sentences adopted in Bahasa Indonesia? What kind of Arabic phrases and sentences adopted in Bahasa Indonesia? What are the changes in the Arabic phrases and sentences adopted in Bahasa Indonesia? This is a library research by collecting all the Arabic phrases and sentences found in Bahasa Indonesia compiled in the main resources, “Kamus Bahasa Indonesia Kontemporer” by Drs. Peter Salim and Yenny Salim, books on religion, literature, magazine, newspaper, speech in Bahasa Indonesia and conversation among speaker of Bahasa Indonesia as the secondary resource. The finding of research says that the number of Arabic phrase and sentences adopted in Bahasa Indonesia is 505 phrases or idiomatic sentences. The phrases and sentences have been adjusted in three aspects, mainly: phonetic, syntactical and semantic.Keywords: Tarakiib, Ta’tsiir, Al-Lughah Al-Indunisiyyah